ILMU ASBAB AL-WURUD MEMAHAMI HADIS SECARA KOMPREHENSIF - St. Johariyah (Al-Tafaqquh: Journal of Islamic Law, 2020)
Islamic law is inseparable from the rules of Islam itself as an implementation of the massages of Allah contained in His words is also the hadith of the messenger of Allah peace be upon him. That’s the qur’an and hadith as the two main sources in Islamic law. Therefore, both these sources must be understood comprehensively of with examine first the various branches of the discipline of the science of hadith which is related, one of them is the asbab al-nuzul and asbab al-wurud. Asbab-wurud al-hadith compiled scholars mutakhirin to overcome the various problems associated with matan that can cause in the understanding of the hadiths of the Prophet peace be upon him. This study will present a classification of asbab al-wurud, books realeted, some examples and the benefits of knowing asbab al-wurud.